Breeding for resistance to maize streak virus: challenges, progress and future directions: a review - Mushayi, Malven; Shimelis, Hussein; Derera, John; Tesfamariam, Seltene Abady (Frontiers in Plant Science, 2025)
Maize (Zea mays L.) is a commodity crop sustaining livelihoods and economies globally. However, maize productivity is challenged by many factors. Maize streak virus disease (MSV) is the most damaging in sub-Saharan Africa (SSA). It causes grain yield losses of up to 100% when susceptible varieties are grown without protection. MSV also affects the quantity and quality of crop biomass and silage production. Therefore, there is a need for effective MSV control strategies to minimize both crop yield and quality losses. Breeding and deploying MSV-resistant varieties is the most sustainable, cost-effective, and amenable control measure, especially for smallholder growers. Hence, breeding for MSV resistance in maize varieties targeted for the smallholder sector in SSA is an integral component of most breeding programs in the region. The aim of this review is to document the challenges posed by MSV, management options, breeding approaches, and progress, as well as provide recommendations and future directions. To gain insight into the host-pathogen interaction for parental selection and breeding, the first section of the paper discusses the impact, biology, host range, symptoms and epidemiology of MSV. The second section reviews breeding progress and research gaps in new variety design with MSV resistance as part of the product profiles. The paper reveals the breeding sources of genetic variation, quantitative trait loci, major- and minor-effect genes for MSV resistance and the disease control in maize. Finally, the review highlights the conventional and modern breeding methods, innovations and prospects for MSV resistance breeding. The review would guide scientists and maize breeders in developing and deploying MSV-resistant maize varieties.